Michael Bleaney. Underconsumption theories : a history and critical analysis. Nueva York : International Publishers, 1976 - Lustig, Nora (Estudios Demográficos y Urbanos, 1978)
MICHAEL BLEANEY, Under consumption Theories: A History and Criticai Analysis, Nueva York, International Publishers, 1976.